UNDERSTANDING ALCOHOL ADDICTION: MECHANISM, CONSEQUENCES AND MANAGEMENT - S. Gangasagre, Nagnath; R. Pandhare, *Ravindra; Lahankar, S.; Mirajkar, S.P.; Salve, Nilesh M. (International Journal of Ayurveda and Pharma Research, 2017)
Forensic medicine and toxicology is branch which deals with the study of poison and its treating measure. Forensic medicine is considered as Agadtantra and Vidhivyadyak in Ayurveda. Alcohol is treated as poison (neurotoxic cerebral inebriant poison) when consume much more dose and as medicine in limited dose. In today's era alcohol addiction is very common, most of youth and student addicted to alcohol but also the aged person becoming addicted to it due to today's stress full life style e.g. educational stress, family stress and job stress thats why they addicted to alcohol for false relaxation or pleasure. Alcohol consumption effects on both the quantity and quality of human life, it has consequences for health and well-being. Approximately 90 percent of absorbed alcohol is oxidized in the liver, harm cause to liver which leads to cirrhosis of liver which is incurable. Excessive intake of alcohol, person is so much under its influence that, he loses control over his mental faculties, he is unable to perform the duties on which he is engaged at particular time, and he may be source of danger to himself or the others. This review article deals with how the addiction takes place control of the normal individual, how alcohol deleteriously acts on the body, what effect of alcohol produce on every system of the body, how much quantity of alcohol proved to be fatal for an individual, what short term and long term effect of alcohol addiction, its complications readdiction techniques and much more, this articles conclude that the health hazardous effect of alcohol addiction and important of its timely managements.